Rates of piscivory predict pharyngeal jaw morphology in a piscivorous lineage of cichlid fishes. Issue 4 (10th June 2015) - Burress, Edward D.; Duarte, Alejandro; Serra, Wilson S.; Loureiro, Marcelo
Abstract: The pharyngeal jaw apparatus is a key innovation hypothesised to increase foraging efficiency and facilitate utilisation of novel resources among teleost fishes. Here, we tested whether dietary characteristics could predict pharyngeal jaw morphology among eight species of Neotropical Crenicichla . Additionally, we tested the hypothesis that pharyngeal jaws may impose a functional constraint on piscivory via pharyngeal gape. We quantified the shape of the lower pharyngeal jaw (LPJ) using linear and geometric morphometrics and quantified diet using the relative volumetric proportions of prey items. We used principal component analysis to describe major axes of variation in LPJ shape and dietary patterns. The major axis of dietary variation significantly predicted LPJ morphology, which was driven by a significant relationship between LPJ shape and rates of piscivory. We also found that rates of piscivory predicted size‐corrected LPJ depth. Size‐corrected pharyngeal gape also significantly predicted rates of piscivory such that pharyngeal jaws may constrain piscivory by limiting pharyngeal gape. Strong form‐to‐function linkage between pharyngeal morphology and trophic patterns suggests an adaptive quality of the pharyngeal apparatus but may also impose functional constraints when consumers must switch prey or when prey availability is temporally or spatially unpredictable.